1991
DOI: 10.1016/1010-7940(91)90103-q
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis in non-cardiac thoracic surgery: Cefazolin versus placebo

Abstract: A total of 127 patients (57 given placebo and 70 given a single preoperative dose of 1 g cefazolin) undergoing thoracic surgery were included in a randomized double-blind trial. The two groups were similar in regard to mean age, sex ratio, in-hospital stay before surgery, underlying disease, risk factors, type of surgery, mean duration of surgical procedure, and mean duration of chest tube drainage. The relative risk of wound infection of the patients from the placebo group was 3.27 (range 1.5-11.5; 95% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 9 publications
0
27
1
3
Order By: Relevance
“…The overall incidence of surgical site infections (4%) and empyema (6%) in the entire study population of the current study was lower than that reported in the study by Aznar et al [5] . This is because medical thoracoscopy is generally a much shorter and less extensive procedure than thoracic surgery.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…The overall incidence of surgical site infections (4%) and empyema (6%) in the entire study population of the current study was lower than that reported in the study by Aznar et al [5] . This is because medical thoracoscopy is generally a much shorter and less extensive procedure than thoracic surgery.…”
Section: Discussioncontrasting
confidence: 54%
“…Surgical site infection occurred in 1 subject (2%) in the antibiotic group and 3 subjects (6%) in the saline group ( p = 0.62); empyema occurred in 3 subjects (6%) in each group ( p = 1.00). There was no association between age, comorbid illness (diabetes mellitus or chronic kidney was found to be effective in reducing the wound infection rate in noncardiac thoracic surgery [5] . In another study, a single dose of 1.5 g of cefuroxime given preoperatively did not reduce the incidence of postoperative infection in patients undergoing thoracic surgery as compared to no antibiotic use [7] .…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations